2006
DOI: 10.1103/physrevb.74.085408
|View full text |Cite
|
Sign up to set email alerts
|

Migration of point defects at charged Cu, Ag, and Au (100) surfaces

Abstract: We report ab initio values for the electrical dipole moment and for the formation and activation energies of adatoms and vacancies migrating on Cu, Ag, and Au ͑100͒ surfaces, and we discuss the effect of the electrical dipole energy of these point defects on the rate of mass transport along charged metal-electrolyte interfaces. We find that adatoms and vacancies exhibit positive surface dipole moments, which for positive electrode potentials tend to reduce the formation and activation energies and increase the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 28 publications
(37 reference statements)
4
28
0
1
Order By: Relevance
“…To assess the effect of the potential f in the second case, we consider the adatom formation energy, which has a potential-dependent electrostatic contribution of p Z e 0 À1 C d f, where C d is the differential capacitance and p Z the dipole moment of the metal adatom. [14] Using p Z = 0.092 e , calculated for Cu adatoms on bare Cu(100) [15] and C d = 25 mC cm À2 , [16] this energy contribution is 0.26 eV V À1 . The corresponding change in the Cu ad surface concentration for a potential increase Df is exp (p Z e 0 À1 C d Df/ k B T), which would result in a 125 % increase for Df = 80 mV at room temperature.…”
mentioning
confidence: 99%
“…To assess the effect of the potential f in the second case, we consider the adatom formation energy, which has a potential-dependent electrostatic contribution of p Z e 0 À1 C d f, where C d is the differential capacitance and p Z the dipole moment of the metal adatom. [14] Using p Z = 0.092 e , calculated for Cu adatoms on bare Cu(100) [15] and C d = 25 mC cm À2 , [16] this energy contribution is 0.26 eV V À1 . The corresponding change in the Cu ad surface concentration for a potential increase Df is exp (p Z e 0 À1 C d Df/ k B T), which would result in a 125 % increase for Df = 80 mV at room temperature.…”
mentioning
confidence: 99%
“…For the adatom dipole moment, we use 0.05 eÅ. This is less than the 0.2 eÅ for a tungsten adatom on the most densely packed tungsten plane ͑110͒, reported by Besocke and Wagner, 19 and also smaller than the ϳ0.1 eÅ calculated by Müller and Ibach 16 for the ͑100͒ planes of the fcc materials Au, Cu, and Ag, which also have a higher packing density than the ͑100͒ plane of the bcc structure of tungsten. For W͑110͒, step line tension data are available 20 and range from 0.1 to 0.3 eV/ Å depending on the step orientation.…”
Section: Application To Schottky Emittersmentioning
confidence: 89%
“…Key to this approach is the change in the local charge density at the surface upon the creation of an adatom. 16 The charge redistribution induced by an adatom can be characterized with a dipole moment p and it changes the work function of the surface:…”
Section: Step Model Including the Effect Of An Extraction Voltagementioning
confidence: 99%
“…However, simulations by Feibelman on Al(100) [2] as well as Yu and Scheffler on Au(100) [3] indicated that on both surfaces exchange diffusion is the predominant process for migration along terraces. The case of Au(100) has been reconsidered by Müller and Ibach, [4] who concluded that on an uncharged surface both mechanisms occur with comparable frequency.…”
Section: Introductionmentioning
confidence: 97%